Nebulization of the acidified sodium nitrite formulation attenuates acute hypoxic pulmonary vasoconstriction - Surber Mark W; Hoglen Niel C; Elliott Garry T; Dahal Bhola K; Schermuly Ralph T; Egemnazarov Bakytbek; Weissmann Norbert; Grimminger Friedrich; Seeger Werner; Ghofrani Hossein A (Respiratory Research, 2010)
Abstract Background Generalized hypoxic pulmonary vasoconstriction (HPV) occurring during exposure to hypoxia is a detrimental process resulting in an increase in lung vascular resistance. Nebulization of sodium nitrite has been shown to inhibit HPV. The aim of this project was to investigate and compare the effects of nebulization of nitrite and different formulations of acidified sodium nitrite on acute HPV. Methods Ex vivo isolated rabbit lungs perfused with erythrocytes in Krebs-Henseleit buffer (adjusted to 10% hematocrit) and in vivo anesthetized catheterized rabbits were challenged with periods of hypoxic ventilation alternating with periods of normoxic ventilation. After baseline hypoxic challenges, vehicle, sodium nitrite or acidified sodium nitrite was delivered via nebulization. In the ex vivo model, pulmonary arterial pressure and nitric oxide concentrations in exhaled gas were monitored. Nitrite and nitrite/nitrate were measured in samples of perfusion buffer. Pulmonary arterial pressure, systemic arterial pressure, cardiac output and blood gases were monitored in the in vivo model. Results In the ex vivo model, nitrite nebulization attenuated HPV and increased nitric oxide concentrations in exhaled gas and nitrite concentrations in the perfusate. The acidified forms of sodium nitrite induced higher levels of nitric oxide in exhaled gas and had longer vasodilating effects compared to nitrite alone. All nitrite formulations increased concentrations of circulating nitrite to the same degree. In the in vivo model, inhaled nitrite inhibited HPV, while pulmonary arterial pressure, cardiac output and blood gases were not affected. All nitrite formulations had similar potency to inhibit HPV. The tested concentration of appeared tolerable. Conclusion Nitrite alone and in acidified forms effectively and similarly attenuates HPV. However, acidified nitrite formulations induce a more pronounced increase in nitric oxide exhalation.